A systematic review of structural MRI investigations within borderline personality disorder: Identification of key psychological variables of interest going forward. (April 2020) - Davies, Geoff; Hayward, Mark; Evans, Simon; Mason, Oliver
Highlights: There are existing meta-analyses investigating grey matter volume in Borderline Personality Disorder (BPD) however these have focused on studies comparing BPD participants with control participants. The present paper offers a novel contribution to the field as it is the first to synthesize and investigate across study protocols how psychological variables relate to structural neurobiology in the disorder. The paper also offers a novel protocol for assessing study quality in MRI research . We believe this offers a valid method based on the comprehensive, gold standard MRI reporting guidelines of CORBIDAS. It is both user-friendly and clear for future researchers to use. The manuscript also offers real world, systematic and clear recommendations for the future directions in imaging research within BPD. Abstract: Existing models of Borderline Personality Disorder (BPD) suggest that a combination of genetic vulnerability, childhood trauma, and disrupted attachment can lead to the marked emotional lability, impulsivity and interpersonal difficulties observed clinically. Brain structural differences in frontal, limbic and hippocampal regions have been reported in BPD. Less clear is how specific psychological factors relate to these structural differences, and how consistently this is found across studies. This was the focus of the present review. Eighteen studies published between 2004 and 2018 met inclusion criteria encompassing 990 participants. Study quality was assessed using the Nottingham-Ottawa Scale. We also introduce a newly devised scale to assess MRI reporting quality. The most frequently investigated psychological variable were impulsivity (9 studies), depression (8), trauma (6), aggression (6), severity of symptoms (3), global functioning, abuse and dissociation (2). Study quality varied, however, a trend was observed where newer studies were higher in reporting quality. Impulsivity demonstrated greater association with frontal structures, trauma related to the hypothalamus and limbic systems, and aggression with hippocampal and frontal structures. The present review recommends greater exploration of neurocognitive and psychosis-related features such as delusions, paranoia and voice-hearing in future studies, and to investigate cortical changes in longitudinal designs.